Analisis Kesiapan Guru dalam Melaksanakan Proses Belajar Mengajar di Kelas - Wote, Alice Yeni Verawati; Sabarua, Jefrey Oxianus (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2020)
The learning process must continue to be carried out with efforts to meet educational service standards. In the efforts made, there are several things that are still obstacles, including related to the quality of learning which must be the basic principle of education. Indications of the low quality of learning in class are strongly influenced by the lack of readiness of teachers. In principle, the purpose of this study is to identify a description of the readiness of the teacher in carrying out learning in the classroom; and designing the readiness of the teacher in creating optimal learning in the classroom. This type of research is descriptive qualitative. The data sources of this research were 5 teachers, a place for learning activities and texts (documents). Data collection techniques using questionnaires, interviews, observation and collection of supporting documents. The analysis technique used in this research is interactive analysis. The results of the analysis show that the description of the readiness of the teacher in carrying out classroom learning at SD GMIH Lina Ino is that the five respondents have met the competence from the aspect of personality. Meanwhile, the aspects of learning tools and classroom management are still in a condition that is quite close to lacking, including the condition of the classrooms that are lacking in facilities to support the implementation of the learning process. The design of the design of teacher readiness in creating optimal learning at SD GMIH Lina Ino is by optimizing 2 aspects which include, Learning Tools and Classroom Management; and supporting factors (classroom conditions), considering that the five respondents had the greatest deficiencies in the ability to manage the class. In addition, learning tools are also weak indicators as well as indicators of classroom conditions.